34 Decreased opportunities to approach next of kin for eye donation to the liverpool research eye bank due to COVID-19. (16th November 2022) - Levis, Hannah; Moss, Samantha; Mount, Laura; Kaye, Stephen
Abstract : Background: The Liverpool Research Eye Bank (LREB) specialises in collection and storage of ocular tissues for use in projects investigating ophthalmic diseases and potential treatments. In collaboration with the Liverpool Eye Donation Centre (LEDC), we collect whole eyes from cadaveric donors. The LEDC screens potential donors and approaches next-of-kin for consent on behalf of the LREB; however, there are factors which reduce the pool of donors such as transplant suitability, time constraints, medical contraindications and other complications. During the past 21 months, COVID-19 has been a big contraindication to donation. The study aimed to determine how much of an impact COVID-19 has had on donations to the LREB. Methods: Between January 2020 and October 2021, the LEDC compiled a database detailing the results of decedent screen at The Royal Liverpool University Hospital Trust site. From these data the suitability of each decedent for transplant, research or unsuitable for both was extrapolated along with the number of decedents unsuitable specifically due to having COVID-19 at the time of death. Data on the number of families then approached regarding donation for research, the number who gave consent and the number of tissues collected were also included. Results: The LREB did not collect any tissues from decedents who had COVID-19 listed on their death certificate during 2020 and 2021. The number of unsuitable donors for transplant or research increased considerably due to COVID-19 positivity, in particular, during the months of Oct 2020-Feb 2021. This led to decreased approaches being made to next of kin. Interestingly, COVID-19 did not appear to have directly affected the number of donations. The number of donors consented ranged from 0-4 per month throughout the 21 months, with no correlation to the months when COVID-19 deaths were at their highest. Conclusions: The lack of an association between COVID-19 cases on donor numbers suggests that the donation rates are influenced by other factors. Increasing awareness of the opportunity for donation for research may increase donation rates. Development of informational materials and organisation of outreach events will aid in this goal.